Neurosarcoidosis: a review from diagnosis and future perspectives - Westendorp, Willeke F.; van de Beek, Diederik; Brouwer, Matthijs C. (EClinicalMedicine, 2025)
Sarcoidosis is complicated by neurosarcoidosis in 5–15% of cases. Neurosarcoidosis is characterized by the presence of non-necrotizing granulomas that can affect any part of the nervous system. Key clinical presentations include chronic meningitis, cranial nerve palsies, parenchymal cerebral and spinal lesions, peripheral neuropathy, or myopathy. Diagnosis requires histopathological confirmation of granulomatous disease and exclusion of other potential diagnoses. Immunosuppressive treatment strategies are based on cohort studies and expert consensus, as randomized controlled trials are lacking. Neurosarcoidosis is associated with high morbidity, with only one third of patients being symptom-free status after treatment. Optimal care should be centralized to provide specialized multidisciplinary expertise and facilitate research. Future research should focus on the optimal timing of 3rd line treatment initiation and treatment personalization. The Netherlands Organisation for Health Research and Development (ZonMw), European Research Council.